PECULIARITIES OF THE CRIME OF DRIVING A VEHICLE UNDER THE INFLUENCE OF PSYCHOACTIVE SUBSTANCES, PROVIDED BY ART. 336 PARA. (2) CP. THEORETICAL AND PRACTICAL ASPECTS - Alexandru STAN (Challenges of the Knowledge Society, 2023)
In the current social and legal context, the crime provided by art. 336 para. (2) CP is increasingly common in the practice of criminal investigation bodies and courts. Both theorists and practitioners have been faced with problems of interpretation of the incriminated text, regarding the meaning of the notion of psychoactive substances, the way in which the influence that these substances have on the ability to drive a vehicle or detention in competition of this crime with the one provided by art. 4 of Law no. 143/2000. The present paper aims to analyze the controversial aspects stated above, both from a theoretical and a practical point of view. The opinions of legal authors in the matter will be presented and interpreted, as well as the solutions pronounced by the High Court of Cassation and Justice, by other national courts and by the criminal prosecution bodies. The present study will present, with regard to each controversial aspect to which I have referred, both the authors conclusions and possible proposals for lege ferenda. At the same time, the possibility of ensuring the uniform interpretation of the incriminated text by all courts will be analyzed, regarding all the aspects that were the subject of this paper.